ANALISIS PERKENIBANGAN KINERJA LAPORAN KEUANGAN PADAPERUSAHAANTELEKOMUNIKASIYANGLISTNG DI BURSA EFEK JAKARTA - Lucia Ika Fitriastuti (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2011)
The purpose of this study was to analyze trends in the financial statements on the performance of telecommunications companies listed on the stock exchanges Indonesia for 5 years. In determining the sample using purposive sampling method. The samples used were 5 companies from 2006 to 2010. Calculated using the ratio of liquidity, activity, leverage, profitability and market. Thefinancial ratios for 5 years were analyzed and compared changes seen conditions ofthe industry average. This study concludes that thefinancial performance of telecommunications companies in general are good. Trend financial performance of telecommunications companies are relatively constant and trend financial ratios from year to year is getting better.